Newly discovered Late Cretaceous adakites in South Fujian Province: Implications for the late Mesozoic tectonic evolution of Southeast China. (3rd January 2018) - Zhao, Xilin; Jiang, Yang; Xing, Guangfu; Yu, Minggang; Mao, Jianren; Yu, Shengyao
Abstract : The Yongchun pluton is a Late Cretaceous adakitic intrusion in South Fujian Province, Southeast China, with associated metal mineralization. An understanding of the Yongchun pluton is helpful in tectono‐magmatic evolutionary processes, and is important in explaining the origin of related porphyry‐type deposits. Zircons from three samples of the pluton were analyzed by laser ablation–inductively coupled plasma–mass spectrometry (LA–ICP–MS), yielding U–Pb ages of 99.50 ±0.87 Ma, 97.74 ±0.59 Ma, and 99.65 ±0.92 Ma. These ages are similar to those of the Sifang, Luoboling, and Sukeng plutons, all of which are related to Cu–Pb–Zn–Mo mineralization within the study area. The Yongchun pluton comprises high‐potassium, calc‐alkaline, metaluminous rocks, with average A/CNK values of 0.91, 87 Sr/ 86 Sr ratios of 0.705 51 to 0.706 83, εNd(t) values of −4.63 to −5.90, and two‐stage Nd model (T2DM ) ages of 1.49–1.39 Ga, indicating the magmas were generated by partial melting of Mesoproterozoic continental crust mixed with mantle‐derived magmas. The pluton has geochemical characteristics typical of adakites, such as a high Sr content (average 553 ppm), and low Y (average 15.2 ppm) and Yb (average 1.61 ppm) contents, indicating that the parental magma was formed under high‐pressure conditions. The magmatism was associated with thickening of the lower crust during a change in subduction angle and convergence rate of the paleo‐Pacific Plate at 100 Ma. The compression was limited to South Fujian Province. Abstract : The Yongchun pluton is a Late Cretaceous adakitic intrusion in South Fujian Province, Southeast China, with an associated metal mineralization. The pluton were generated by partial melting of Mesoproterozoic continental crust mixed with mantle‐derived magmas. The magmatism was associated with thickening of the lower crust during a change in subduction angle and convergence rate of the paleo‐Pacific Plate at 100 Ma. Abstract : 中国南東, 福建省南部のYongchun 深成岩は後期白亜紀のアダカイト質の貫入岩であり, 金属の鉱化を伴っている. Yongchun 深成岩は, この周辺地域の地質構造やマグマの進化過程を理解し, それに伴う斑岩タイプ(鉱床)の堆積物の成因を説明する上で重要である. 深成岩の三試料から得られたジルコンはLA‐ICP‐MSにより分析され, それらのウラン鉛年代は, それぞれ, 99.50 ±0.87 Ma, 97.94 ±0.59 Ma, 99.65 ±0.92 Maであった. これらの年代はSifang全角LuobolingおよびSukeng深成岩類に類似しており, 銅—鉛—亜鉛—マンガンの鉱化作用とも関連している. この深成岩は高カリウムのカルクアルカリ岩であり, アダカイト質(高Sr, 低Y, Yb)の特徴を持ち, 高圧での地殻の融解を示唆している. この火成活動は全角約一億年前の古太平洋プレートの沈み込み角度や沈み込み速度の変化とそれにともなう下部地殻の肥厚に関係しているかもしれない.